Possible Involvement of a Tetrahydrobiopterin in Photoreception for UV‐B‐induced Anthocyanin Synthesis in Carrot. (16th July 2014) - Takeda, Junko; Nakata, Rieko; Ueno, Hiroshi; Murakami, Akio; Iseki, Mineo; Watanabe, Masakatsu
Abstract Our previous studies of action spectra for UV‐B‐induced anthocyanin accumulation in cultured carrot cells indicated that a reduced form of pterin, possibly tetrahydrobiopterin, contributes to UV‐B photoreception. In this report, we provide additional evidence for the involvement of pterin in UV‐B light sensing. UV‐B‐induced phenylalanine ammonia‐lyase (PAL) activity was considerably suppressed by N‐acetylserotonin (an inhibitor of tetrahydrobiopterin biosynthesis), and this suppression was partially recovered by adding biopterin or tetrahydrobiobiopterin. In addition, protein(s) specifically bound to biopterin were detected by radiolabeling experiments in N‐acetylserotonin‐treated cells. Furthermore, diphenyleneiodonium, a potent inhibitor of electron transfer, completely suppressed UV‐B‐induced PAL activity. These results suggest the occurrence of an unidentified UV‐B photoreceptor (other than UVR8, the tryptophan‐based UV‐B sensor originally identified in Arabidopsis) with reduced pterin in carrot cells. After reexamining published action spectra, we suggest that anthocyanin synthesis is coordinately regulated by these two UV‐B sensors.